Studi Kasus Permasalahan Sosial Pemalu Pada Anak Yang Tidak di Asuh Oleh Orang Tua (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This article aims to determine the form of shyness problems in the subject, analyze the influencing factors and the impact of shyness on the subject. This research uses a qualitative method with a case study approach, while data collection tools use observation, interviews and documentation. The subject in this research was 1 child aged 6 years. The results of the research show that Z experiences problems with shyness, including not joining in activities that involve lots of people, liking activities that he does alone, not wanting to appear in front of the class, and a tendency to speak at a low volume.